IMP dehydrogenase rod/ring structures in acral melanomas. (13th January 2020) - Keppeke, Gerson D.; Barcelos, Denise; Fernandes, Mariana; Comodo, Andréia N.; Guimarães, Daiane P.; Cardili, Leonardo; Carapeto, Fernando C. L.; Andrade, Luis E. C.; Landman, Gilles
Abstract: Acral lentiginous melanoma (ALM) is a rare subtype of melanoma with aggressive behavior. IMPDH enzyme, involved in de novo GTP biosynthesis, has been reported to assemble into large filamentary structures called rods/rings (RR) or cytoophidium (cellular snakes). RR assembly induces a hyperactive state in IMPDH, usually to supply a high demand for GTP nucleotides, such as in highly proliferative cells. We investigate whether aggressive melanoma tumor cells present IMPDH‐based RR structures. Forty‐five ALM paraffin‐embedded tissue samples and 59 melanocytic nevi were probed with anti‐IMPDH2 antibody. Both the rod‐ and ring‐shaped RR could be observed, with higher frequency in ALM. ROC curve analyzing the proportions of RR‐positive cells in ALM versus nevi yielded a 0.88 AUC. Using the cutoff of 5.5% RR‐positive cells, there was a sensitivity of 80% and specificity of 85% for ALM diagnosis. In ALM, 36 (80%) showed RR frequency above the cutoff, being classified as RR‐positive, compared with only 9 (15%) of the nevi ( p  < .001). Histopathology showed that 71% of the RR‐positive specimens presented Breslow thickness > 4.0mm, compared with only 29% in the RR‐low/negative ( p  = .039). We propose that screening for RR structures in biopsy specimens may be a valuable tool helping differentiate ALM from nevi and accessing tumor malignancy.